High level of interleukin-32 gamma in the joint of ankylosing spondylitis is associated with osteoblast differentiation. Issue 1 (December 2015) - Lee, Eun-Ju; Lee, Eun-Jin; Chung, Yeon-Ho; Song, Da-Hyun; Hong, Seokchan; Lee, Chang-Keun; Yoo, Bin; Kim, Tae-Hwan; Park, Ye-Soo; Kim, Soo-Hyun; Chang, Eun-Ju; Kim, Yong-Gil
Abstract Backgound The formation of bony spurs and ankylosis is a key pathognomic feature in ankylosing spondylitis (AS) and results in functional impairment. The aim of this study was to investigate the role of IL-32γ in osteoblast (OB) differentiation and its association with the pathogenesis of AS. Methods The concentration and expression of IL-32γ were evaluated in synovial fluid and tissue from patients with AS, rheumatoid arthritis (RA) and osteoarthritis (OA), using enzyme-linked immunosorbent assay and immunohistochemistry. To establish whether IL-32γ affects OB differentiation, we used calvarial cells ofIL-32γ transgenic (TG) mice or wild-type (WT) mice. To elucidate the mechanism of osteoblastogenesis, levels of regulators were assayed inIL-32γ TG mice and in primary OBs after IL-32γ stimulation. Results The IL-32γ levels were higher in the synovial fluid of AS patients compared with RA or OA patients and the expression of IL-32 was higher in AS synovia than in RA or OA synovia. Additional IL-32γ stimulation in precursor cells enhanced OB differentiation potentially andIL-32γ TG mice showed higher rates of OB differentiation than WT mice. IL-32γ reduced the expression of DKK-1, a negative regulator, in both WT precursor cells and human OBs and the constitutive expression of DKK-1 was suppressed in calvarial cells fromIL-32γ TG mice. Conclusions The elevated level of IL-32γ in AS joint could enhance OB differentiation via DKK-1 suppression. Therefore, IL-32γ might be a putative molecular target to prevent the abnormal bone formation in AS.